Penerapan Model Problem Based Learning Untuk Melihat Nilai Kreatif Siswa Menggunakan Soal AKM Numerasi Pada Materi Aritmatika Sosial di SMP - Safei; Aisyah, Nyimas (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
An issue that is currently being hotly discussed in the world of education is the value of character, especially in learning mathematics. One component of character values in mathematics learning is creative values. Creative values in mathematics learning are categorized as values that rarely appear compared to other character values, so this is contrary to the goals of the Indonesian people who want to welcome the skills of the 21st century. Problem Based Learning is a solution to encourage students' creative values in learning mathematics, supported by Minimum Competency Assessment (AKM) questions which are in line with the government's targets in preparing students to welcome the XXI century. This research aims to determine students' creative value in learning social arithmetic material in class VII using AKM Numeracy questions with the application of the problem based learning model. The creative values that are the focus of this research are the creative values of flexibility, fluency, risk-taking, and appreciative. The research subjects were class VII students at SMP Negeri 45 Palembang. Data was collected through tests, observations and interviews, then analyzed qualitatively. The results of the research state that the creative values that most often appear in learning social arithmetic material in Problem Based Learning using AKM Numeracy questions are apprectiative, risk-taking, and flexibility, while the creative value that rarely appears is fluency.